DUANE’S SYNDROME: SURGICAL OUTCOME AND NON OPHTHALMOLOGIC ASSOCIATIONS - Sarfraz, Sarah; Zafar, Saemah Nuzhat; Khan, Ayesha (Journal of Ayub Medical College Abbottabad, 2014)
Background: Duane retraction syndrome (DRS) is the most common of the ocular congenital cranial dysinnervation disorders .This study evaluates the types of Duane syndrome and its management in patients presenting to the paediatric and strabismus unit of a tertiary care eye hospital. Methods: This case series study involved 41 patients diagnosed with Duane syndrome between January 2007 and December 2009. History of presenting complaints, past treatment and family history were recorded. Ocular examination and orthoptic assessment was carried out Results: Forty one patients were included in this case series study. It involved 10 right eyes, 27 left eyes and both eyes of 4 patients. There were 26 females and 15 males. Type-1 Duane syndrome was present in 28 (68.3%), type 2 in 8 (19.5%), Type-3 in 4 (9.8%) and type-4 with synergistic divergence was present in 1 (2.4%) patient. Comorbidity was present in 6(14.6%) patients. Surgery was carried out in 26 (63.4%) patients either for abnormal head posturing or significant upshoots or down shoots. Upshoots noted in 21 eyes, were completely or partially resolved in 15 cases. Among 4 patients with down shoots on adduction, complete resolution was seen in 1. The pre and post-operative measurements of horizontal deviation showed statistically significant difference in Duane type-1 and 2, where as in Duane type-3 it was not significant. One patient with type-4 Duane did not undergo surgery. Conclusions: Recession of the horizontal recti is more effective in treating the upshoot or down shoot associated with DRS as compared to recession and y-split of the horizontal muscle. Keywords: Duane retraction syndrome, upshoots and downshoots, congenital cranial dysinnervation disorder